Analysis of MreB interactors in Chlamydia reveals a RodZ homolog but fails to detect an interaction with MraY - Ouellette, Scot P.; Rueden, Kelsey J.; Gauliard, Emilie; Persons, Logan; de Boer, Piet A.; Ladant, Daniel (Frontiers in Microbiology, 2014)
Chlamydia is an obligate intracellular bacterial pathogen that has significantly reduced its genome in adapting to the intracellular environment. One class of genes for which the bacterium has few annotated examples is cell division, and Chlamydia lacks FtsZ, a central coordinator of the division apparatus. We have previously implicated MreB as a potential substitute for FtsZ in Chlamydia (Ouellette et al., 2012). Thus, to identify new chlamydial cell division components, we searched for proteins that interacted with MreB. We performed a small-scale screen using a Gateway® compatible version of the Bacterial Adenylate Cyclase Two Hybrid (BACTH) system, BACTHGW, to detect proteins interacting with chlamydial MreB and identified a RodZ (YfgA) homolog. The chlamydial RodZ aligns well with the cytoplasmic domain of E. coli RodZ but lacks the periplasmic domain that is dispensable for rod cell shape maintenance in E. coli. The expression pattern of yfgA/rodZ was similar to that of mreB and ftsI, suggesting that these genes may operate in a common functional pathway. The chlamydial RodZ correctly localized to the membrane of E. coli but was unable to complement an E. coli rodZ mutant strain, likely because of the inability of chlamydial RodZ to interact with the native E. coli MreB. Finally, we also tested whether chlamydial MreB could interact with MraY, as suggested by Gaballah et al. (2011). However, we did not detect an interaction between these proteins even when using an implementation of the BACTH system to allow native orientation of the N- and C-termini of MraY in the periplasm. Thus, further work will be needed to establish this proposed interaction. In sum, we have added to the repertoire of potential cell division proteins of Chlamydia.